Strategi Pengelolaan Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Pendapatan Asli Desa Kembang Kerang di BUMDes Bina Sejahtera - Linda Sriwahyuni; Nining Purwati; Syawahid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Village-Owned Enterprises (BUMDes) are institutions established or formed by the village government whose capital ownership and management are carried out by the village government together with the village community. This research aims to determine the management strategy of BUMDes in utilizing local economic potential with various types of village potential to improve the welfare of village communities and contribute to village original income. This research uses triangulation with the processes that have been carried out, namely, data/document collection; interviews; analyzing the data that has been obtained. The results of the research show that BUMDes in increasing village revenue and BUMDes in improving community welfare is extraordinary because BUMDes Bina Sejahtera can provide community services. BUMDes Bina Sejahtera has a function as a facilitator and server and BUMDes Bina Sejahtera is expected to be more innovative in developing the management of existing village local economic potential.